Exploring Complementary Leadership Styles in Madrasahs by Aiming at Their Impact on Integrity and Character Development - Abdullah Ataman; Hasan Baharun; M Aqil Fahmi Sanjani; Sevia Diana Safitri (Business and Applied Management Journal, 2024)
This study aims to explore the role of madrasah principal leadership in shaping students' character through an approach based on Islamic values. This study is based on the importance of character development in the madrasah educational environment that not only emphasizes academic achievement, but also the formation of students' morals according to Islamic teachings. This study was conducted using a qualitative method through semi-structured interviews and observations of two madrasah principals under the auspices of the Pondok Pesantren Education and Social Foundation. The results of the study indicate that the principal applies an exemplary and disciplined approach to build a madrasah culture that values integrity, while the principal of Madrasah Diniyah uses a humanist approach by establishing close personal relationships with students. The contribution of these findings shows that different but complementary leadership strategies can create a conducive learning environment for student character development, and emphasizes the importance of integrity and empathy in building trust between leaders, staff, and students in madrasahs. This study is expected to provide practical insights for madrasah managers in optimizing a leadership approach that is in accordance with the context of education based on Islamic values.